Effect of letrozole added to gonadotropins in controlled ovarian stimulation protocols on the yield and maturity of retrieved oocytes. (3rd April 2019) - Ben-Haroush, Avi; Wertheimer, Avital; Klochendler, Emilie; Sapir, Onit; Shufaro, Yoel; Oron, Galia
Abstract: We aimed to evaluate the effect of co-administration of letrozole and gonadotropins during ovarian stimulation on oocyte yield and maturation in breast cancer patients prior to chemotherapy. A retrospective cohort design was used comparing oocyte cryopreservation cycles among patients with breast cancer patients with other oncological indications and women undergoing elective oocyte cryopreservation. All patients were treated with GnRH antagonist protocol using GnRH agonist for final oocyte maturation. The breast cancer group was additionally treated with letrozole (5 mg/d) from the first day of treatment until the day of oocyte retrieval. The cohort included 418 patients: 145 breast cancer patients, 168 with other oncological indications, and 105 patients who chose to undergo elective oocyte cryopreservation. There were no significant differences among the groups in the number of retrieved oocytes or proportion of mature oocytes. On multivariate linear regression models, co-treatment with letrozole was not a significant factor for the number of retrieved oocytes or for oocyte maturation rate after controlling for age, body mass index (BMI), and FSH dose. We conclude that the addition of letrozole to gonadotropins does not increase the number of oocytes retrieved or the oocyte maturation rate.